Peran Kepuasan Pelanggan Dalam Memediasi Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pelanggan PDAM Kota Baubau - Winton, Kuswinton; Sukrin, Sukrin; Aswira, Resfika; Haryanto, Abel (Akademi Sekretari Manajemen Taruna Bakti, 2023)
The phenomenon that occurs is that the level of leakage in the use of PDAM is relatively high, especially during the peak hours of water use. Because it is profit-oriented so that social services or functions are reduced. Then the community complaints that occur are the amount of water distributed to the community. The purpose of this study is to explain the effect of service quality on customer loyalty with customer satisfaction as the intervening variable. The population in this study amounted to 895 customers. The sampling technique uses a simple random sample of 90 customers and is analyzed using SmartPLS version 3.0. The results of the study show that service quality has no significant effect on customer loyalty. Service quality has a significant effect on customer satisfaction. Service quality has a significant effect on customer loyalty. Customer satisfaction is able to mediate the effect of service quality on customer loyalty.